Always, already: present tense in J.M. Coetzee’s disgrace - Seyed Javad Habibi; Sara Soleimani Karbalaei (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper is an attempt to bring up some typological aspects of the fictional works with the present tense narratives. By focusing on J.M. Coetzee’s novel Disgrace (2000), as an example of this type of narrative, Henri Bergson’s notion of time (Duration) is assumed as the temporal framework for the novel. Besides, analysing the inadequacy of Henry James’ definition of plot in terms of the present tense narratives, a new type of framework referred as “pattern”is introduced and its relation with Bergson’s Duration and Kristeva’s intertextuality is highlighted. As a finale to this study, the dovetail joining of the stream-of-consciousness narrative technique and the present tense narrative is accented.